Determinants of Innovative Work Behavior among Digital MSME Employees: The Roles of Entrepreneurial Leadership and Digital Mindset - Putra, Riskia; Rosyidi, Achmad Kholif; Syahputra, Denny Prabu (Journal of Office Administration : Education and Practice, 2026)
This study examines the determinants of innovative work behavior among employees of digital micro, small, and medium-sized enterprises (MSMEs), focusing on the roles of entrepreneurial leadership and digital mindset. A quantitative explanatory research design was employed, with data collected from 120 employees of digital MSMEs in East Java Province. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that entrepreneurial leadership does not have a statistically significant direct effect on innovative work behavior. However, entrepreneurial leadership significantly influences employees’ digital mindset, which in turn has a positive and significant effect on innovative work behavior. Furthermore, mediation analysis reveals that digital mindset mediates the relationship between entrepreneurial leadership and innovative work behavior, with an indirect effect of 0.060, indicating full mediation. These results suggest that the influence of entrepreneurial leadership on innovative work behavior operates primarily through cognitive mechanisms rather than direct effects. From a theoretical perspective, this study extends social learning theory by demonstrating the central role of digital mindset in linking leadership and innovation within technology-driven work environments. From a practical perspective, the findings highlight the importance for leaders of digital MSMEs to foster employees’ digital mindset as a strategic means of enhancing sustainable, innovative work behavior.